Peran Pembelajaran IPA Berbasis Kearifan Lokal dalam Memotivasi Minat Belajar di Sekolah Dasar - Indriyani, Wahyu Erni; Fajrie, Nur; Fathurohman, Irfai (Journal Prakarsa Paedagogia, 2024)
This article discusses the activities of class VI SD N 3 Karangaji Jepara in science lessons regarding changes in objects. Problems that exist include uninteresting learning and a lack of student activity and interest in learning. This activity aims to see the role of science teaching and learning activities based on traditional knowledge in motivating interest in learning in grade VI elementary schools Semester 1 of SD N 3 Karangaji Kedung Jepara for the 2023/2024 academic year. This type of study is an in-depth qualitative methodology with a descriptive. Results of students' interest in learning which was originally low and has increased. The culture of the region where students are located potential that students have to be effective.originally low and has increased. The culture of the area where students live potential that students have to be effective.dituliskan maksimal 150 kata dalam bahasa inggris dengan font 10 pt Garamond. Struktur abstrak dimulai dari tujuan penulisan/penelitian, kebaruan dari artikel, dan hasil penelitian/ simpulan akhir hasil kajian.